The religiosity gap: preferences for seeking help from religious advisors - Crosby, James William (Mental health, religion & culture, 2012)
As unique cultural variables receive increasing attention in the extant psychotherapy and counselling literature, religiosity seems an apt target for continued close examination. In a sample of 235 college students, the current study focused on variables associated with preferences for seeking help from a religious advisor (for psychological distress), rather than the help of a psychological professional. Results indicated that religiosity accounted for the most variance (R 2 = 0.20) in preferences for religious help-seeking (PReHS). Additionally, the perceived benefits of self-disclosure, religious involvement, mental illness stigma, and attachment anxiety all accounted for much smaller amounts of unique variance in PReHS. Practitioners are encouraged to consider internal aspects of religiosity (e.g., thoughts and beliefs) at intake and throughout treatment, in addition to more external aspects such as religious affiliation and church attendance. Limitations, implications for future research, and conceptualisations of religiosity in mental health care are discussed.